MANAGEMENT OF ECONOMICAL POTENTIAL OF ENTERPRISE - I. I. Chvankova (Литьë и металлургия)
Two directions of the economical potential investigation are presented in the article. The identification of conceptions '‘enterprises potential” and reserves is given. The latest points of view of the leading native specialists for the enterprise financial state are taken into account in this article.